Evaluation Of The Youth Posyandu Program In The Coastal Area Of Bentiring Health Center Bengkulu City - Pila Kartika; Wulandari Wulandari; Fery Surahman (Journal Hygeia Public Health, 2026)
Background: The Youth Posyandu is a community-based health service effort aimed at improving the health status of adolescents through promotive and preventive measures. Although this program has been implemented in various regions, its execution is still not optimal, including in the coastal area of Bentiring Health Center in Bengkulu City. The purpose of this research is to evaluate the implementation of the Youth Posyandu Program based on three main aspects: input, process, and output.Research Method: The method used is qualitative descriptive with a case study approach. The informants in the study consist of the head of the health center, program officers, cadres, and adolescent participants of the Posyandu. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and qualitative conclusion drawing.Research Results: The results show that the input aspect still has weaknesses, such as a lack of trained personnel, minimal special funding, and insufficient supporting facilities. In the process aspect, planning and implementation of activities have not been maximized due to a lack of adolescent involvement and the absence of routine evaluations. From the output aspect, the attendance and participation rates of adolescents are still low, although there is an increase in knowledge among some adolescents who actively participate.Recommendations: The researchers recommend that Bentiring Health Center enhance cadre training, optimize facilities and infrastructure, strengthen adolescent participation through ongoing education, and conduct routine monitoring and evaluation to make the Youth Posyandu Program more effective and sustainable.